Influence of iron ore concentrate (magnetite) on the kinetics of butadiene–styrene rubber-based blend curing in the presence of different accelerators - A. A. Khachaturov; E. E. Potapov; S. V. Reznichenko; A. N. Kovaleva (Тонкие химические технологии, 2020)
Objectives. To investigate the possibility of using a cheaper ingredient, such as magnetite, in the synthesis of rubber compounds based on butadiene–styrene rubber by examining its effect on the process of sulfuric vulcanization of butadiene–styrene rubber in the presence of various accelerators.Methods. The influence of magnetite on the vulcanization kinetics was studied using an Alpha Technologies PRPA 2000 rotorless rheometer. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) were performed using a Mettler Toledo TGA/DSC 2 device to evaluate the effect of magnetite on the butadiene–styrene rubber-based vulcanizates’ oxidation.Results. Magnetite was found to affect the kinetics of SBR-1500 butadiene–styrene rubber sulfuric vulcanization in the presence of thiazole-type accelerators (2-MBT, 2-MBS); in contrast, magnetite was inactive in the case of diphenylguanidine, sulfenamide T, and tetramethylthiuram disulfide. The obtained TGA/DSC data showed that magnetite has no significant effect on the butadiene–styrene rubber-based vulcanizates’ oxidation and thermal destruction.Conclusions. The obtained data confirmed magnetite’s capability to act as a butadiene–styrene rubber sulfuric vulcanization activator in the presence of various accelerators. The most significant effect was observed in the presence of thiazole-type accelerators.